Watershed Development a major element for achieving Goals of Pradhan Mantri Krishi Sinchayee Yojana: Present Scenario - PANDEY, C. M. (Journal of Soil and Water Conservation, 2020)
Soil and water conservation interventions of watershed development programmes are extremely important for achieving goals. In this paper an attempt has been made to collect the efforts of Government of India through programmes for conservation and management of land and water and its impact in sustaining soil fertility and foodgrains production along with its long term residual impact of various kind of land uses. After detailed analysis and review of recent document and annual reports, it is evident that most of programmes on soil, water conservation and management (watershed programmes) are closed or subsumed under Paramparagat Krishi Vikas Yojana (PKVY)/Pradhan Mantri Krishi Sinchayee Yojana (PMKSY). Accordingly, project implementing agencies are required to approach concerned department both at national and state levels for funding. As these interventions are major driving elements for sustaining soil fertility and foodgrain production therefore it’s planning and implementation has to be in accordance to District Agriculture/ Irrigation plans approved for respective districts across the country.